(untitled) (Indian Journal of Biochemistry and Biophysics (IJBB), 2023)
Histamine is a biogenic amine which is synthesised by L-histidine decarboxylase enzyme (HDC). The histamine 1 and 2 antagonist administrations have been highly reported to cause detrimental effect on sperm parameters, which arisen the speculation of histamine 1 (H1R) and histamine 2 (H2R) receptors might be present in sperm. The present study was aimed to provide evidence on the localisation of H1R and H2R on mice sperm through immunocytochemistry. The sperm was harvested from cauda epididymis. After one hour of incubation, sperm suspension was smeared onto a poly-lysine-coated slide and allowed to dry before fixation and permeabilisation processes. The primary antibody encoded for receptors was exposed to the fluorescently tagged antibody; fluorescein isothiocyanate (FITC) conjugate followed by nuclear staining with 4, 6-diamino-2-phenylindole dihydrochloride (DAPI). The testis, stomach, and skin were used as the positive controls. Our data showed that both receptors have been expressed on the midpiece and acrosome of mice. The present result was the first discovery of the presence and immunolocalisation of H1R and H2R on mice sperm. Therefore, present study proposes that these receptors could be involved in calcium regulatory mechanism and protein phosphorylation which are responsible for fertilisation-related processes.